2017
DOI: 10.1063/1.4985997
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the drop/interface partial coalescence with surfactants

Abstract: This paper presents investigations on the partial coalescence of an aqueous drop with an organicaqueous interface with and without surfactants. The organic phase was different silicone oils and the aqueous phase was a glycerol-water solution at different concentrations. It is found that when the surfactant Span 80 is introduced into the organic phase, the partial coalescence region is reduced in the Oh-Bo coalescence map. The range of the inertio-capillary regime reduces when surfactants are present, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…4a shows a much larger pressure difference ΔP ≈ 12 across the interface in the columnarregion as compared to the neck-region of the droplet. Similar large pressure gradient in the liquid column is also reported in the numerical studies of Dong et al [18] and Martin and Blanchette [29]. Thus, the pressure-force induced upward pull on the droplet is more than the radial push at the neck, leading to the shrinkage of the droplet near the neck at faster rate than the downward-collapse that results in the break-up near the neck and formation of secondary drop at = 0.58 .…”
Section: Flow Dynamics: Numerical Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…4a shows a much larger pressure difference ΔP ≈ 12 across the interface in the columnarregion as compared to the neck-region of the droplet. Similar large pressure gradient in the liquid column is also reported in the numerical studies of Dong et al [18] and Martin and Blanchette [29]. Thus, the pressure-force induced upward pull on the droplet is more than the radial push at the neck, leading to the shrinkage of the droplet near the neck at faster rate than the downward-collapse that results in the break-up near the neck and formation of secondary drop at = 0.58 .…”
Section: Flow Dynamics: Numerical Resultssupporting
confidence: 77%
“…Particle Image Velocimetry (PIV) experiments by Kassim and Longmire [17] were used to quantify the velocity and vorticity fields during the coalescence events of drops in different viscous fluids. Using the high speed shadowgraphy, Dong et al [18] observed the evolution of the interfaces and drop size ratios during a partial coalescence of an aqueous drop with an organicaqueous interface with and without surfactant. They used PIV for velocity profiles and vorticity structures in the coalescing drops.…”
Section: Introductionmentioning
confidence: 99%
“…A stopwatch with an accuracy of 0.01s was used to measure the rest times. It was previously found that about 50 runs were sufficient to capture the distribution of the rest times of the drops with a stationary interface (Dong et al 2017(Dong et al , 2019). In the current experiments, around 200 runs were conducted for each set of conditions to reduce uncertainties caused by the moving interface.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…In as early as 1881, Reynolds discussed this phenomenon and indicated that impurities of the surface might lead to coalescence (Reynolds 1881). In contrast, later studies found an increase of the drop rest time when detergents or surfactants were added (Yeo & Matar 2003;Dai & Leal 2008;Dong et al 2017Dong et al , 2019. In fact, surfactants are widely used to stabilize emulsions or dispersions (Sajjadi et al 2002;Li et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…55 Surfactants can enhance or weaken partial coalescence effects, depending on the concentrations and the induced surface elasticity. [56][57][58][59][60][61] For our system, inertia is negligible and there are no propagating capillary or elastic waves induced by the droplet motion. Although the dependence of contact time on droplet radius Dt B R 3/2 as observed by e.g.…”
Section: Discussionmentioning
confidence: 98%